Preparation and Study of Poly(Vinylidene Fluoride-Co-Hexafluoropropylene)-Based Composite Solid Electrolytes - Meihong Huang; Lingxiao Lan; Pengcheng Shen; Zhiyong Liang; Feng Wang; Yuling Zhong; Chaoqun Wu; Fanxiao Kong; Qicheng Hu (Crystals)
Solid-state electrolytes are widely anticipated to revitalize lithium-ion batteries with high energy density and safety. However, low ionic conductivity and high interfacial resistance at room temperature pose challenges for practical applications. This study combines the rigid oxide electrolyte LLZTO with the flexible polymer electrolyte poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) to achieve effective coupling of rigidity and flexibility. The semi-interpenetrating network structure endows the PEL composite solid electrolyte with excellent lithium-ion transport capabilities, resulting in an ionic conductivity of up to 5.1 × 10−4 S cm−1 and lithium-ion transference number of 0.41. The assembled LiFePO4/PEL/Li solid-state battery demonstrates an initial discharge capacity of 132 mAh g−1 at a rate of 0.1 C. After 100 charge–discharge cycles, the capacity retention is 81%. This research provides a promising strategy for preparing composite solid electrolytes in solid-state lithium-ion batteries.